Participation of OCRL1, and APPL1, in the expression, proteolysis, phosphorylation and endosomal trafficking of megalin: Implications for Lowe Syndrome - Sandoval, Lisette; Fuentealba, Luz M.; Marzolo, María-Paz (Frontiers in Cell and Developmental Biology, 2022)
Megalin/LRP2 is the primary multiligand receptor for the re-absorption of low molecular weight proteins in the proximal renal tubule. Its function is significantly dependent on its endosomal trafficking. Megalin recycling from endosomal compartments is altered in an X-linked disease called Lowe Syndrome (LS), caused by mutations in the gene encoding for the phosphatidylinositol 5-phosphatase OCRL1. LS patients show increased low-molecular-weight proteins with reduced levels of megalin ectodomain in the urine and accumulation of the receptor in endosomal compartments of the proximal tubule cells. To gain insight into the deregulation of megalin in the LS condition, we silenced OCRL1 in different cell lines to evaluate megalin expression finding that it is post-transcriptionally regulated. As an indication of megalin proteolysis, we detect the ectodomain of the receptor in the culture media. Remarkably, in OCRL1 silenced cells, megalin ectodomain secretion appeared significantly reduced, according to the observation in the urine of LS patients. Besides, the silencing of APPL1, a Rab5 effector associated with OCRL1 in endocytic vesicles, also reduced the presence of megalin's ectodomain in the culture media. In both silencing conditions, megalin cell surface levels were significantly decreased. It is known that megalin phosphorylation, mediated by GSK3ß, reduces receptor recycling. Here we focus on insulin signaling that reduces GSK3ß activity. Accordingly, megalin phosphorylation was significantly reduced by insulin in wild-type cells. Moreover, in OCRL KD cells, even though the insulin response was reduced, the phosphorylation of megalin was decreased, and the cell surface increased, suggesting a protective role of insulin in a LS cellular model.